(untitled) (Research, Society and Development, 2022)
Introduction: The full use must be done with appropriate cooking techniques in order to improve the supply of nutrients in meals, according to the principles of healthy eating. Objective: To analyze the ways of making full use of food and its impact on population health. Methodology: This is a literature review with an integrative approach. Results: From the literature study, it was possible to observe that the full use of food and its impact on population health, it is important for the nutritionist to understand the theme that has become increasingly known. It is also possible to form critical and reflective thinking, considering that the nutritional contribution contained in reused foods directly influences the life of human beings. Discussion of the results: It was presented the effective existence of using food in its entirety means more than economy, it means using available resources without waste, recycling, respecting nature and eating well, with pleasure and dignity. Conclusion: Through the studies carried out, it was possible to prove that the full use of food can contribute to the development of a healthy and balanced lifestyle.